Diretrizes para um sistema de medição de desempenho para empresas do ramo madeireiro da região amazônica norte mato-grossense : estudo multicasos - Fedato, Geovana Alves de Lima (2010)
This work assumes that to effectively manage business activities, a form of control and monitoring is necessary, whether by means of indicators, or in a more advanced situation, by means of a performance measurement process that is suitable to the company s reality. Thus, the objective of this study is to establish guidelines for develop a performance measurement system, capable of assisting the peculiarities and organizational needs of control and strategies for companies in the wood sector in the city of Sinop, in Mato Grosso, Brazil. Companies currently face several challenges, because they need to thrive in a highly competitive environment, concomitantly meeting the needs and expectations of multiple stakeholders. This paper addresses the importance of environmental and social variables, which are currently increasing and whose reflexes on the organization are no longer latent but obvious. The method used to achieve the goals was the multiple case study with a qualitative approach, which enabled to identify the companies selected, and from this reality, to establish guidelines for develop a performance measurement system for two scenarios, was first proposed for the method of Rouse e Putterill (2003) for companies without an adequate infrastructure to measure performance. The second applies the Performance Prism framework by Neely et al. (2002) for companies with more suitable infrastructure for the development of a system performance measurement more robust. In all the companies of the scenario, social and environmental issues can be included, hence representing the reality under study in a clearer manner. The contribution the academy is conducted to compare the characteristics of performance measurement and management infrastructure, already contributing to the logging companies was made to suggest ways to control and evaluation of activities that respect the maturity of the management and peculiarities of each.